Using Value Stream Costing to Improve Oil Extraction Operations: A Field Study on Akakus Oil Operations Company (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to examine the effectiveness of Value Stream Costing in improving oil extraction operations at Akakus Oil Operations Company, by analyzing costs across value stages and linking them to value-generating activities in order to enhance operational efficiency and reduce waste. The problem of the study arises from the company’s reliance on traditional costing systems that focus on financial recording without analyzing sources of loss or measuring added value, which limits management’s ability to improve performance in a complex, multi-stage operational environment. Accordingly, the central research question is: to what extent can Value Stream Costing be employed as a strategic tool to support the costing system and enhance the efficiency of extraction operations? The importance of the study lies in presenting a practical framework for applying this approach in the oil sector, providing accurate information that supports operational and strategic decision-making, and addressing a knowledge gap related to the limited research applications of this method in extractive industries. The study adopted a descriptive-analytical methodology, relying on field data and statistical analysis to test both the main and subsidiary hypotheses.   The results revealed that the main hypothesis was partially confirmed, as a statistically significant relationship was found between the application of Value Stream Costing and the improvement of extraction operations. Some subsidiary hypotheses were fully validated, such as the relationship between cost analysis across value stages and operational efficiency, while others were only partially confirmed, such as the relationship between waste reduction and overall performance improvement. This reflects practical challenges related to data accuracy and resistance from traditional systems. These findings affirm that Value Stream Costing provides a more comprehensive perspective than conventional systems, yet requires institutional support to ensure its full effectiveness.  Based on these results, the study recommends restructuring the costing system to rely on value streams rather than functional departments, integrating Value Stream Costing into accounting information systems to ensure data accuracy, implementing specialized training programs for staff to strengthen application capacity, and adopting value stream maps as a continuous monitoring tool to identify sources of waste and reassess performance. Furthermore, the study calls for expanding future research to apply this approach in other industrial sectors to promote sustainability.
Keywords: Value Stream Costing; Oil Extraction; Operational Efficiency; Waste Reduction; Akakus Oil Company